Three- and two-point spatial correlations of IGM at z ∼ 2: cloud-based analysis using simulations. Issue 4 (19th September 2020) - Maitra, Soumak; Srianand, Raghunathan; Gaikwad, Prakash; Choudhury, Tirthankar Roy; Paranjape, Aseem; Petitjean, Patrick
ABSTRACT: Ly α forest absorption spectra decomposed into multiple Voigt profile components (clouds) allow us to study clustering of intergalactic medium (IGM) as a function of H i column density ($N_{\rm H\, \small{I}}$ ). Here, we explore the transverse three-point correlation (ζ) of Ly α clouds using mock triplet spectra from simulations at z ∼ 2 on scales of 1–5 h −1 cMpc. We find ζ to depend strongly on $N_{\rm H\, \small{I}}$ and scale and weakly on angle of the triplet configuration. We show that the 'hierarchical ansatz' is applicable for scales $\ge ~ 3\, h^{-1}$ cMpc, and obtain a median reduced three-point correlation (Q) in the range 0.2–0.7. We show, ζ is influenced strongly by the thermal and ionization state of the gas. As in the case of galaxies, the influence of physical parameters on Q is weaker compared to that on ζ. We show difference in ζ and Q between different simulations are minimized if we use appropriate $N_{\rm H\, \small{I}}$ cut-offs corresponding to a given baryon overdensity (Δ) using the $N_{\rm H\, \small{I}}~versus~Δ$ relationship obtained from simulations. We study the effect of pressure broadening on ζ using a model with artificially boosted heating rates. However, for models with realistic thermal and ionization histories the effect of pressure broadening on ζ is subdominant compared to other local effects. We find the strong redshift evolution shown by ζ, mainly originating from the redshift evolution of thermal and ionization state of the IGM. We discuss the observational requirements for the detection of three-point correlation, specifically, in small intervals of configuration parameters and redshift.